Association between folate metabolism-related polymorphisms and colorectal cancer risk - KIM, JONG WOO (Mol Clin Oncol, 2015)
Folate has essential roles in DNA synthesis, repair and methylation. Folate metabolism-related gene variants may modulate the levels of this vitamin and affect the cancer risk. Thus, whether these polymorphisms play an important role in carcinogenesis, particularly colorectal cancer (CRC) development, has been a subject interest. The present study investigated the association between polymorphisms in the methylenetetrahydrofolate reductase (MTHFR), thymidylate synthase (TS) and the reduced folate carrier 1 (RFC1) genes and CRC risk. Polymorphisms in MTHFR (677C>T and 1298A>C), TS [1494del6 and the TS enhancer region (TSER)] and RFC1 (−43T>C, 80G>A and 696C>T) were characterized using polymerase chain reaction-restriction fragment length polymorphism in 477 CRC cases and 514 controls. Although no polymorphisms were significantly associated with the CRC risk in the overall sample, significant associations between folate metabolism-related polymorphisms and CRC risk were identified in the stratified analyses. The MTHFR 677CT/1298AC and MTHFR 1298AC+CC/TSER 2R3R genotypes in the presence of plasma folate levels ≤4.12 ng/ml were associated with significantly increased CRC risk. In addition, individuals with the MTHFR 677TT/TSER 3R3R or MTHFR 677/TSER 3R3R/TS 1494 0bp6bp+6bp6bp genotypes and diabetes mellitus (DM) were at an increased risk for CRC. Therefore, the data suggest that i) MTHFR polymorphisms combined with low plasma folate levels and ii) polymorphisms in folate metabolism-related genes combined with metabolic syndrome risk factors (hypertension and DM) increase the odds of developing CRC.